Doctors’ experiences of providing care in rural hospitals in Southern New Zealand: a qualitative study - Hedman, Mante; Doolan-Noble, Fiona; Stokes, Tim; Brännström, Margareta (BMJ open, 2022)
ObjectiveTo explore rural hospital doctors’ experiences of providing care in New Zealand rural hospitals.DesignThe study had a qualitative design, using qualitative content analysis.SettingThe study was conducted in South Island, New Zealand, and included nine different rural hospitals.RespondentsSemistructured interviews were conducted with 16 rural hospital doctors.ResultsThree themes were identified: ‘Applying a holistic perspective in the care’, ‘striving to maintain patient safety in sparsely populated areas’ and ‘cooperating in different teams around the patient’. Rural hospital care more than general hospital care was seen as offering a holistic perspective on patient care based on closeness to their home and family, the generalist perspective of care and personal continuity. The presentation of acute life-threatening low-frequency conditions at rural hospitals were associated with feelings of concern due to limited access to ambulance transportation and lack of experience.Overall, however, patient safety in rural hospitals was considered equal or better than in general hospitals. Doctors emphasised the central role of rural hospitals in the healthcare pathways of rural patients, and the advantages and disadvantages with small non-hierarchical multidisciplinary teams caring for patients. Collaboration with hospital specialists was generally perceived as good, although there was a sense that urban colleagues do not understand the additional medical and practical assessments needed in rural compared with the urban context.ConclusionsThis study provides an understanding of how rural hospital doctors value the holistic generalist perspective of rural hospital care, and of how they perceive the quality and safety of that care. The long distances to general hospital care for acute cases were considered concerning.